1997
DOI: 10.1086/304920
|View full text |Cite
|
Sign up to set email alerts
|

Astrometric Detection of a Low‐Mass Companion Orbiting the Star AB Doradus

Abstract: We report submilliarcsecond-precise astrometric measurements for the late-type star AB Doradus via a combination of VLBI (very long baseline interferometry) and HIPPARCOS data. Our astrometric analysis results in the precise determination of the kinematics of this star, which reveals an orbital motion readily explained as caused by gravitational interaction with a low-mass companion. From the portion of the reÑex orbit covered by our data and using a revised mass of the primary star (0.76 M _) derived from our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 20 publications
2
60
0
Order By: Relevance
“…However, the binarity of AB Dor B itself with a separation of only 0.7 (called AB Dor Ba and AB Dor Bb) was detected only after the advent of adaptive optics. Yet another low-mass companion to AB Dor A is AB Dor C Guirado et al (1997), located about 0.16 away from AB Dor A.…”
Section: Our Target Starmentioning
confidence: 99%
“…However, the binarity of AB Dor B itself with a separation of only 0.7 (called AB Dor Ba and AB Dor Bb) was detected only after the advent of adaptive optics. Yet another low-mass companion to AB Dor A is AB Dor C Guirado et al (1997), located about 0.16 away from AB Dor A.…”
Section: Our Target Starmentioning
confidence: 99%
“…Its age is estimated to be 20-30 Myr (Guirado et al 1997;Collier Cameron & Foing 1997), and Innis et al (1986) suggested that AB Dor is member of the Pleiades based on its space velocity. The main physical parameters of AB Dor are shown in Table 1.…”
Section: Ab Dormentioning
confidence: 99%
“…Our final DEMs are corrected for the distances of the stars: we have adopted D ¼ 14:9 pc (Guirado et al 1997) and D ¼ 48 pc (de Bruijne et al 2001) for AB Dor and V471 Tau, respectively.…”
Section: Algg Orithm and Line Selectionmentioning
confidence: 99%
“…Precise astrometry of the orbital motion of stars in binary systems allows us to obtain accurate, model-independent estimates of the masses of the individual components, relevant to provide tests of stellar evolution models (Guirado et al 1997;Torres et al 2012;Reid & Honma 2014). In the case of low-and very-lowmass stars, only a handful of stellar systems with dynamicallydetermined masses have been reported (Hillenbrand & White 2004;Stassun et al 2004;Mathieu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Given its high-level of radio emission, during the early 90's AB Dor A was monitored astrometrically with VLBI as part of a program to link the optical reference frame, defined by the positions of the stars observed by the ESA's astrometric satellite Hipparcos (Lindegren & Kovalevsky 1995;Lestrade et al 1995), and the celestial reference frame, defined by VLBI positions (Lestrade et al 1995). The VLBI-Hipparcos combined data revealed the presence of a low-mass companion, 0.090 M , AB Dor C (Guirado et al 1997), orbiting AB Dor A at an average angular distance of 0.2 . Imaging this new low-mass companion was difficult and it had to wait until the VLT near-infrared observations carried out by Close et al (2005Close et al ( , 2007 using commissioning time of the Simultaneous Differential Imager (SDI) at the VLT, which allowed independent photometry of AB Dor C, free from contamination of the much brighter AB Dor A.…”
Section: Introductionmentioning
confidence: 99%